Out of Touch? Challenges in Reconnecting Bodies with Instruments 'of the Future'. - Harper, Adam (Contemporary Music Review, 2020)
'Touch', and the return of the body to digital music-making in general, has taken on a central importance in electronic instrument design and theory in recent decades. 'Touch' and lack thereof has been considered central to the challenge of a 'disconnect' between musicians' bodily actions and digital instruments, and as a solution to it that instruments 'of the future' can provide. But 'touch' is not a universal quantity; it is a construction that varies widely in its application and invocation, across academic and commercial contexts of instrument design. This article examines the complex history of the contemporary concern with 'touch', and its role in the framing and reception of instruments such as ROLI's Seaboard, JazzMutant's Lemur, Sensel's Morph and the Joué. With reference to writings on embodied cognition, the recent material turn in the humanities and to Mills and Sterne's concept of dismediation it seeks to historicise, interrogate, and denaturalise 'touch' within instrument design and its surrounding discourse.